On the transverse magnetization of the anisotropic superconductor 2H-NbSe2: Дефекты в кристаллах - Sirenko, V. A.; Makedonska, N. I.; Shabakayeva, Yu. A.; Schleser, R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
Torque measurements were performed on a high-quality single crystal of the uniaxial superconductor 2H-NbSe2 in a tilted magnetic field 0-200 kG, in the temperature range1.5-4.2 K. The transverse component of the absolute magnetization was derived in a magnetic field directed at an angle of 77° to the axis of anisotropy, and its field dependence was analyzed in a reversible domain of the mixed state. The penetration depth and anisotropy characteristics were obtained for the sample under study.